Rwanda : Request for a Three-Year Policy Support Instrument; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2010)
Rwanda has achieved high growth and macroeconomic stability under three successive Poverty Reduction Growth Facility (PRGF) arrangements. Executive Directors welcomed the new Private Sector Investment (PSI) program, which aims to consolidate macroeconomic stability and achieve sustained broad-based growth while reducing Rwanda's aid dependency. They emphasized that this can be achieved by maintaining sustainable fiscal position, strengthening monetary and exchange rate policies, and supporting growth with structural reforms. In view of this, Directors approved a three-year PSI for Rwanda for preserving macroeconomic stability, consistent with the authority's poverty reduction and growth strategy, Economic Development and Poverty Reduction Strategy (EDPRS).